INTERDEPENDENCE OF TOURISM DIVERSIFICATION AND REGIONAL DEVELOPMENT FEATURES OF KAZAKHSTAN - Panzabekova , A.Zh. (Academic Journal of Physical and Chemical Sciences, 2018)
This work is aimed at identifying of the interdependence of tourism and regional features of Kazakhstan development. To achieve the set goal, the methods of system approach, scientific abstraction, analysis, synthesis, and comparison were applied. The paper shows the most perspective regions and trends of tourist activity, and assesses the contemporary state of tourism in Kazakhstan regions. To estimate the diversification correlation of tourism by regional features, the social and economic indicators of regions development were considered. The results of the research showed that tourism development in Kazakhstan regions is extremely uneven. As a consequence of this, the authors have determined several macro-regions that have its own pronounced features – South, North, Central-East, West regions, and Almaty, and Astana cities. It is shown that tourism diversification in each of them should be oriented on its factors